Current collector, secondary battery, electric device and preparation method of current collector
By adopting a multi-layer design current collector in the secondary battery, combining the intermediate layer and surface layer of high-content metal elements, the problem of difficult to take into account both energy density and cycle life in the prior art is solved, and higher cycle life and safety performance are achieved.
Patent Information
- Application Number
- CN202411124874.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-15
AI Technical Summary
While increasing the energy density, existing secondary battery current collectors often sacrifice cycle life, making it difficult to take into account both.
The current collector is designed with a multi-layer design. The intermediate layer is composed of a high-content first metal element (such as Fe, Sn, Ni, Zn), and the surface layer is composed of a high-content second metal element (such as Cu), and the surface layer is deposited by electroplating to control the average grain size and diffraction intensity ratio to take into account the tensile strength and bending resistance.
While maintaining high strength, the bending resistance of the current collector is improved, the time when the secondary battery pole plates produce cracks is delayed, the cycle life is improved, and the safety risks are reduced.
Smart Images

Figure CN119852420A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a current collector, a secondary battery, an electrical device, and a method for preparing the current collector. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] The current collector is an important component of secondary batteries. The improvement of secondary battery energy density often comes at the expense of cycle life. It is urgent to develop a current collector that takes into account both battery energy density and cycle life to meet the needs of the new generation of secondary batteries. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its object is to provide a current collector that can achieve both battery energy density and cycle life.
[0005] The first aspect of the present application provides a current collector, which includes a surface layer and an intermediate layer arranged between the surface layers, the intermediate layer includes a first metal element, and the total mass content of the first metal element is greater than or equal to 80% based on the total mass of the intermediate layer elements, and the surface layer includes a second metal element, and the total mass content of the second metal element is greater than or equal to 80% based on the total mass of the surface layer elements; the tensile strength of the intermediate layer is greater than or equal to the tensile strength of the surface layer, and the bending resistance of the surface layer is greater than or equal to the bending resistance of the intermediate layer.
[0006] The current collector achieves both strength and bending resistance through a multi-layer design. The middle layer has a relatively high tensile strength, and the surface layer has a relatively high bending resistance. The bending resistance of the current collector is improved while maintaining high strength, delaying the time for cracks to form on the pole piece of the secondary battery during the cycle process, thereby increasing the cycle life of the secondary battery and reducing safety risks.
[0007] In any embodiment, the first metal element includes one or more of Fe, Sn, Ni, and Zn.
[0008] The metal material with the above-mentioned first metal element as the main component often has high strength, which is beneficial to improving the tensile strength of the current collector, delaying the time when cracks appear on the outer ring of the pole piece during the cycle process, and is beneficial to improving the cycle life of the battery.
[0009] In any embodiment, the second metal element includes Cu.
[0010] Copper metal materials tend to have high ductility, which helps improve the bending resistance of the current collector, delays the time for cracks to appear in the inner circle of the electrode during the cycle, and helps improve the cycle life of the battery.
[0011] In any embodiment, the average grain size of the surface layer is greater than or equal to 1.7 μm.
[0012] The surface layer with an average grain size within the above range can improve the bending resistance of the current collector and delay the time when cracks appear in the inner ring of the battery cell during the cycle process.
[0013] In any embodiment, the average grain size of the surface layer is 1.7 μm-3.5 μm.
[0014] In any embodiment, the average grain size of the surface layer is 1.9 μm to 2.5 μm.
[0015] The surface layer with an average grain size within the above range can better balance the strength and bending resistance of the current collector, delay the time for cracks to appear in the battery cell during the cycle process, improve the cycle life of the secondary battery, and reduce safety risks.
[0016] In any embodiment, the diffraction intensity of the (111) crystal plane in the surface layer accounts for 20%-40% of the total diffraction intensity of the (111) crystal plane, (200) crystal plane, (220) crystal plane, (311) crystal plane, and (222) crystal plane in the surface layer.
[0017] In the embodiment of the present application, the diffraction intensity of the (111) crystal plane is controlled to account for 20%-40% to improve the bending resistance of the current collector, thereby achieving a balance between the strength and bending resistance of the current collector, increasing the cycle life of the secondary battery and reducing safety risks.
[0018] In any embodiment, the diffraction intensity of the (111) crystal plane in the surface layer accounts for 25% to 35% of the total diffraction intensity of the (111) crystal plane, (200) crystal plane, (220) crystal plane, (311) crystal plane, and (222) crystal plane in the surface layer.
[0019] The diffraction intensity ratio of the (111) crystal plane in the surface layer within the above range can further take into account the strength and bending resistance of the current collector, comprehensively improve the cycle life of the secondary battery, and reduce safety risks.
[0020] In any embodiment, the average grain size of the intermediate layer is 0.1 μm-1 μm.
[0021] The current collector with the average grain size of the middle layer within the above range has higher strength, and can reduce the probability of cracks appearing on the outer circle of the wound battery cell and cracks appearing on the edge of the laminated battery cell.
[0022] In any embodiment, the thickness of the current collector is 3 μm-8 μm.
[0023] The current collector has a low thickness, which can effectively reduce the weight of the battery and is conducive to further improving the energy density of the battery.
[0024] In any embodiment, the thickness of the intermediate layer is 2 μm to 6 μm, and the thickness of the surface layer on one side is 0.5 μm to 2 μm.
[0025] The current collector with the thickness of the intermediate layer and the surface layer within the above range can effectively take into account the strength and bending resistance of the current collector, improve the cycle life of the secondary battery, and enhance the safety of the secondary battery.
[0026] In any embodiment, under the test conditions of room temperature, sample thickness of 6±0.2 μm, and stretching speed of 50±0.5 mm / min, the tensile strength of the current collector is greater than or equal to 900 MPa.
[0027] The current collector has high strength, can improve the anti-expansion ability of the battery core, increase the cycle life of the battery, and improve the safety performance of the battery.
[0028] In any embodiment, under the test conditions of room temperature, sample thickness of 6±0.2 μm, and stretching speed of 50±0.5 mm / min, the tensile strength of the current collector is greater than or equal to 1000 MPa.
[0029] A current collector with a tensile strength greater than or equal to 1000 MPa can reduce the risk of premature cracking at the outer ring or edge of the battery cell due to expansion force during the battery cycle, further improving the safety of the battery.
[0030] In any embodiment, under the test conditions of room temperature, sample thickness of 6±0.2 μm, and stretching speed of 50±0.5 mm / min, the tensile strength of the current collector is 1000 MPa-1250 MPa.
[0031] The current collector with a tensile strength within the above range can take into account both strength and bending resistance, thereby comprehensively improving the cycle life of the battery.
[0032] In any embodiment, under the test conditions of room temperature and a sample thickness of 6±0.2 μm, the current collector can be bent for 7 or more times.
[0033] The above-mentioned current collector has good bending resistance, which can reduce the probability of premature cracking at the bend inside the battery cell, leading to battery failure, and improve the cycle life of the battery.
[0034] In any embodiment, under the test conditions of room temperature and a sample thickness of 6±0.2 μm, the current collector can be bent 7 to 18 times.
[0035] The current collector with a bendable number of times within the above range can take into account both bending resistance and strength, thereby comprehensively improving the cycle life of the battery.
[0036] A second aspect of the present application provides a secondary battery, comprising a pole piece, wherein the pole piece comprises the current collector of the first aspect.
[0037] A third aspect of the present application provides an electrical device, comprising the secondary battery of the second aspect.
[0038] The fourth aspect of the present application provides a method for preparing a current collector, which specifically includes: obtaining an intermediate layer, the intermediate layer including a first metal element, and the mass content of the first metal element is greater than or equal to 80% based on the total mass of the intermediate layer elements; depositing a surface layer on the surface of the intermediate layer to obtain a current collector; the surface layer includes a second metal element, and the mass content of the second metal element is greater than or equal to 80% based on the total mass of the surface layer elements; the tensile strength of the intermediate layer is greater than or equal to the tensile strength of the surface layer, and the bending resistance of the surface layer is greater than or equal to the bending resistance of the intermediate layer.
[0039] The current collector achieves both strength and bending resistance through a multi-layer design. The middle layer has a relatively high tensile strength, and the surface layer has a relatively high bending resistance. The bending resistance of the current collector is improved while maintaining the high strength of the current collector, delaying the time for cracks to appear in the pole piece of the secondary battery during the cycle process, thereby increasing the cycle life of the secondary battery and reducing safety risks.
[0040] In any embodiment, the surface layer is deposited on the surface of the intermediate layer by electroplating, and the electroplating method specifically includes applying current to the electroplating solution so that copper ions in the electroplating solution are reduced and deposited to form the surface layer on the surface of the intermediate layer.
[0041] In any embodiment, the electroplating solution includes an additive, and the additive includes one or more of a leveler, a wetting agent, and a brightener.
[0042] In any embodiment, the additives include leveling agents, wetting agents, and brighteners.
[0043] The above three additives cooperate with each other to prepare a surface layer that makes the current collector have both strength and bending resistance.
[0044] In any embodiment, the concentration of the leveler in the electroplating solution is 40 mg / L-80 mg / L.
[0045] In any embodiment, the concentration of the wetting agent in the plating solution is 30 mg / L-80 mg / L.
[0046] The wetting agent having a concentration in the above range in the electroplating solution is conducive to depositing copper grains of appropriate size on the surface layer, taking into account the strength and bending resistance of the current collector, and improving the cycle life of the secondary battery.
[0047] In any embodiment, the concentration of chloride ions in the plating solution is 30 mg / L-60 mg / L.
[0048] In any embodiment, the concentration of copper ions in the electroplating solution is 50 g / L-100 g / L.
[0049] In any embodiment, the concentration of the brightener in the electroplating solution is 10 mg / L-25 mg / L.
[0050] In any embodiment, the total mass concentration of the leveler and the brightener in the electroplating solution is less than 100 mg / L.
[0051] The leveler and brightener in the electroplating solution with a concentration within the above range is conducive to depositing copper grains of appropriate size on the surface layer, taking into account the strength and bending resistance of the current collector, and improving the cycle life of the secondary battery.
[0052] In any embodiment, the electroplating temperature is 50±5°C.
[0053] In any embodiment, the pH of the electroplating solution is 4-7.
[0054] In any embodiment, the leveling agent includes one or more of gelatin and Janus Green; the wetting agent includes one or more of hydroxyethyl cellulose and polyethylene glycol; the brightening agent includes one or more of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate, and thiourea.
[0055] In any embodiment, the electroplating solution includes gelatin at a concentration of 40 mg / L-80 mg / L, hydroxyethyl cellulose at a concentration of 30 mg / L-80 mg / L, sodium polydisulfide dipropane sulfonate at a concentration of 10 mg / L-25 mg / L, copper ions at a concentration of 50 g / L-100 g / L, and chloride ions at a concentration of 30 mg / L-60 mg / L.
[0056] In any embodiment, the current density of the direct current is 4000A / m 2 -8000A / m 2 The electroplating time is 0.5 minutes to 3 minutes.
[0057] In any embodiment, the preparation method further comprises: heat treating the current collector to obtain an annealed current collector.
[0058] After annealing, the grain size of the current collector further grows, and the diffraction peak intensity ratio of the (111) crystal plane further decreases, which is beneficial to further improve the bending resistance of the current collector, achieve a balance between the strength and bending resistance of the current collector, and comprehensively improve the cycle life of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0060] Figure 1 is a schematic structural diagram of a current collector according to an embodiment of the present application;
[0061] Figure 2 is an inverse pole figure distribution diagram of an electron backscatter diffraction image of the current collector surface according to an embodiment of the present application;
[0062] Figure 3 is an X-ray diffraction pattern of a current collector according to an embodiment of the present application;
[0063] Figure 4 is a schematic diagram of an embodiment of a secondary battery of the present application;
[0064] Figure 5 is an exploded schematic diagram of an embodiment of a secondary battery of the present application;
[0065] Figure 6 is a schematic diagram of an embodiment of a battery module of the present application;
[0066] Figure 7 is a schematic diagram of an embodiment of a battery pack of the present application;
[0067] Figure 8 yes Figure 7 An exploded schematic diagram of an embodiment of a battery pack is shown;
[0068] Fig. 9 is a schematic diagram of an embodiment of an electric device including the secondary battery of the present application as a power source;
[0069] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 secondary battery, 51 housing, 52 electrode assembly, 53 cover plate, 6 current collector, 61 middle layer, 62 surface layer. DETAILED DESCRIPTION
[0070] Hereinafter, the embodiments of the current collector, secondary battery, electrical device and method for preparing the current collector of the present application will be described in detail with appropriate reference to the accompanying drawings. However, there will be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0071] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0072] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0073] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form a new technical solution, and such a technical solution should be deemed to be included in the disclosure of the present application.
[0074] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0075] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0076] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0077] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.
[0078] If not otherwise specified, the values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.
[0079] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.
[0080] In the present application, the terms "plurality" and "multiple" refer to two or more.
[0081] With the increase in the energy density of secondary batteries, there is a demand for thinner and lighter pole piece current collectors. With the thinning of the current collector in the thickness direction, the maximum tensile load that the current collector can withstand decreases, making it difficult for conventional strength current collectors in the prior art to meet the performance requirements of secondary batteries in the long cycle process. With the increase in the number of cycles, under the action of the reciprocating expansion of the pole piece, the wound battery cell using the existing ordinary strength current collector is prone to cracks in the outer ring part where the expansion force is the largest, causing the pole piece to break, resulting in a loose cell structure and displacement of the pole piece; the pole piece fracture is easy to puncture the diaphragm, causing the cell to short internally, resulting in thermal runaway and causing safety accidents. Similarly, stacked cells are prone to cracks at the stress concentration point at the edge of the cell, causing the pole piece to break, causing battery failure and safety problems.
[0082] Increasing the strength of the current collector is beneficial to improving the ability of the battery cell to resist cyclic expansion, and delaying the time when cracks appear in the outer ring or edge of the battery cell, causing the pole piece to break. However, the increase in the strength of the current collector often means that the movement of lattice dislocations inside the current collector is severely hindered, so the brittleness of the current collector increases and the bending resistance deteriorates. Studies have shown that wound batteries using high-strength current collectors are prone to brittle fractures in the inner ring with a large bending degree during the cycle process, which will also cause battery failure. How to improve the strength of the current collector while taking into account the bending resistance of the current collector to delay the occurrence of cracks in the battery cell and the failure of the pole piece, and comprehensively improve the battery cycle life and safety performance has become a technical problem that needs to be solved urgently.
[0083] Based on this, Figure 1 As shown, in the first aspect of the present application, there is provided a current collector 6, which includes a surface layer 62 and an intermediate layer 61 arranged between the surface layers 62, the intermediate layer includes a first metal element, and the total mass content of the first metal element is greater than or equal to 80% based on the total mass of the intermediate layer elements, and the surface layer includes a second metal element, and the total mass content of the second metal element is greater than or equal to 80% based on the total mass of the surface layer elements; the tensile strength of the intermediate layer is greater than or equal to the tensile strength of the surface layer, and the bending resistance of the surface layer is greater than or equal to the bending resistance of the intermediate layer.
[0084] The layer structure of the current collector can be tested by any known method in the art. As an example, the layer structure of the current collector can be characterized by metallographic detection; the cross section of the current collector can also be scanned by a spectrometer combined with argon ion polishing technology and a scanning electron microscope to obtain an element distribution diagram of the current collector cross section. It can be seen that the current collector component provided in the embodiment of the present application presents a multilayer structure in cross section. In the element distribution diagram of the current collector cross section, the surface layer is located on the upper or lower surface of the current collector, and the intermediate layer is arranged between the surface layers in the thickness direction. The element type and mass content of each layer can be obtained by performing an energy spectrum analysis on the cross section or surface of each layer of the current collector. It should be pointed out that the surface layer and the intermediate layer can be identified by the obvious composition boundary in the cross section of the current collector, which does not mean that there must be obvious stratification between the two in the cross-sectional morphology.
[0085] Based on the total mass of the elements in the middle layer, the mass content of the first metal element can be obtained by scanning the middle layer with an energy spectrometer. Based on the total mass of the elements in the surface layer, the mass content of the second metal element can be obtained by scanning the surface layer with an energy spectrometer.
[0086] In some embodiments, the surface layer and the intermediate layer are disposed adjacent to each other in the thickness direction; in some embodiments, any other functional layer is disposed between the intermediate layer and the surface layer. It is understood that the relevant characteristics of the surface layer can be obtained by characterizing the surface layer area in the cross section of the current collector, or by directly characterizing the surface of the current collector.
[0087] In some embodiments, based on the total mass of the intermediate layer elements, the total mass content of the first element may be selected to be 80%, 85%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.98%, 100% or any numerical range therebetween.
[0088] In some embodiments, based on the total mass of the elements in the surface layer, the total mass content of the second metal element may be selected to be 80%, 85%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.98%, 100% or any numerical range therebetween.
[0089] As used herein, the term "tensile strength" refers to the maximum bearing strength of a specimen when continuous loading is applied to the specimen until it breaks.
[0090] In this article, the term "bending resistance" refers to the ability of a sample to resist bending, which can be characterized by the number of times the sample can be bent.
[0091] The tensile strength of the intermediate layer and the surface layer can be tested by any known method in the art. As an example, the surface layer elements of the current collector are etched by any known method to obtain the intermediate layer, and the tensile strength of the intermediate layer and the current collector obtained is tested under the same test conditions. According to the principles of composite material mechanics, the tensile strength of the intermediate layer is greater than or equal to the tensile strength of the current collector, which can indicate that the tensile strength of the intermediate layer is greater than or equal to the tensile strength of the surface layer.
[0092] In the present application, the tensile strength test of the intermediate layer and the current collector can be tested by methods known in the art, such as testing with reference to the GB / T 5230-1995 "Electrolytic Copper Foil" standard. As an example, at least 10 samples with a length of 200±0.5mm, a width of 15±0.25mm, and a thickness of 6±0.2μm are cut, and the samples are continuously loaded at a tensile speed of 50±0.5mm / min at room temperature until they break, and the maximum load divided by the cross-sectional area of the sample is used as the tensile strength of the sample. The cross-sectional area of the sample can be tested by dimensional measurement.
[0093] The bending resistance of the intermediate layer and the surface layer can be tested by any known method in the art. As an example, the surface layer elements of the current collector are etched by any known method to obtain the intermediate layer, and the intermediate layer and the current collector are tested for the number of bends obtained by the same test conditions. According to the mechanics of composite materials, if the number of bends of the current collector is greater than or equal to the number of bends of the intermediate layer, it can be shown that the bending resistance of the surface layer is greater than or equal to the bending resistance of the intermediate layer.
[0094] In the present application, the number of times the intermediate layer and the current collector can be bent can be tested by methods known in the art, such as folding the sample 180°, using a 1.5 kg roller to roll back and forth at the fold, then unfolding it to observe whether cracks appear at the fold to allow light to pass through, and recording the number of rolling times required to cause cracks to appear at the fold to allow light to pass through. Test at least ten samples and take the average value.
[0095] The current collector achieves both strength and bending resistance through a multi-layer design. The middle layer has a relatively high tensile strength, and the surface layer has a relatively high bending resistance. The bending resistance of the current collector is improved while maintaining high strength, delaying the time for cracks to form on the pole piece of the secondary battery during the cycle process, thereby increasing the cycle life of the secondary battery and reducing safety risks.
[0096] In some embodiments, the first metal element includes one or more of Fe, Sn, Ni, and Zn.
[0097] The metal material with the above-mentioned first metal element as the main component often has high strength, which is beneficial to improving the tensile strength of the current collector, delaying the time when cracks appear on the outer ring of the pole piece during the cycle process, and is beneficial to improving the cycle life of the battery.
[0098] In some embodiments, the second metal element includes Cu.
[0099] Copper metal materials tend to have high ductility, which helps improve the bending resistance of the current collector, delays the time for cracks to appear in the inner circle of the electrode during the cycle, and helps improve the cycle life of the battery.
[0100] In some embodiments, the average grain size of the surface layer is greater than or equal to 1.7 μm.
[0101] The average grain size of the surface layer can be tested by methods known in the art. As an example, the surface layer of the current collector (e.g., copper layer) is measured by cross-sectional electron backscatter diffractometer (EBSD) and scanning electron microscope to obtain an inverse pole figure distribution diagram, such as Figure 2 As shown. The grain size of the grains in the reverse pole figure distribution diagram of the current collector surface layer is counted, and a quantity distribution diagram is made. The statistical distribution curve is used for fitting, and the length corresponding to the peak value is taken as the average grain size of the grains. Among them, the grain size is expressed by the equivalent circle diameter of the grains.
[0102] In some embodiments, the average grain size of the surface layer may be 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm or any range therebetween.
[0103] The surface layer with an average grain size within the above range can improve the bending resistance of the current collector and delay the time when cracks appear in the inner ring of the battery cell during the cycle process.
[0104] In some embodiments, the average grain size of the surface layer is 1.7 μm-3.5 μm, and can be optionally 1.9 μm-2.5 μm.
[0105] The surface layer with an average grain size within the above range can better balance the strength and bending resistance of the current collector, delay the time for cracks to appear in the battery cell during the cycle process, improve the cycle life of the secondary battery, and reduce safety risks.
[0106] In some embodiments, the diffraction intensity of the (111) crystal plane in the surface layer accounts for 20%-40% of the total diffraction intensity of the (111) crystal plane, (200) crystal plane, (220) crystal plane, (311) crystal plane, and (222) crystal plane in the surface layer.
[0107] In the present application, the diffraction intensity of the crystal plane in the surface layer can be tested by a method known in the art. As an example, the surface layer is tested by an X-ray diffractometer, referring to the X-ray spectrum of standard copper powder (PDF No.04-0836), such as Figure 3 As shown, the peak area of the diffraction peak located at 40°-45° is taken as the diffraction intensity of the (111) crystal plane, the peak area of the diffraction peak located at 47°-52° is taken as the diffraction intensity of the (200) crystal plane, the peak area of the diffraction peak located at 70°-75° is taken as the diffraction intensity of the (220) crystal plane, the peak area of the diffraction peak located at 85°-95° is taken as the diffraction intensity of the (311) crystal plane, and the peak area of the diffraction peak located at 93°-100° is taken as the diffraction intensity of the (222) crystal plane.
[0108] In some embodiments, the ratio of the diffraction intensity of the (111) crystal plane in the surface layer to the total diffraction intensities of the (111) crystal plane, (200) crystal plane, (220) crystal plane, (311) crystal plane, and (222) crystal plane in the surface layer may be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40% or any numerical range therebetween.
[0109] For crystalline copper, common crystal planes include (111), (200), (220), (311), and (222). According to the crystallographic properties, the (111) crystal plane has a high atomic density and high mechanical strength, which can improve the strengthening effect. The diffraction peak intensity ratio of a crystal plane can be used to characterize the orientation probability of the crystal plane, also known as preferential orientation or preferential orientation. In the prior art, the (111) crystal plane orientation ratio in ordinary strength current collector copper foil is approximately 45% to 55%. The embodiment of the present application improves the bending resistance of the current collector by controlling the diffraction intensity ratio of the (111) crystal plane to 20%-40%, thereby achieving a balance between the strength and bending resistance of the current collector, improving the cycle life of the secondary battery, and reducing safety risks.
[0110] In some embodiments, the diffraction intensity of the (111) crystal plane in the surface layer accounts for 25% to 35% of the total diffraction intensity of the (111) crystal plane, (200) crystal plane, (220) crystal plane, (311) crystal plane, and (222) crystal plane in the surface layer.
[0111] The diffraction intensity ratio of the (111) crystal plane in the surface layer within the above range can further take into account the strength and bending resistance of the current collector, comprehensively improve the cycle life of the secondary battery, and reduce safety risks.
[0112] In some embodiments, the average grain size of the intermediate layer is 0.1 μm-1 μm.
[0113] The average grain size of the intermediate layer can be tested by any known method in the art. As an example, the cross section of the current collector is measured by cross-sectional electron backscatter diffractometer (EBSD) and scanning electron microscope to obtain the inverse pole figure distribution map, and the grain size of the intermediate layer in the cross section is counted to make a number distribution map, and the statistical distribution is used for fitting, and the length corresponding to the peak value is taken as the average grain size of the grain. Among them, the diameter of the equivalent circle of the grain is taken as the grain size.
[0114] In some embodiments, the average grain size of the intermediate layer may be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm or any range therebetween.
[0115] The current collector with the average grain size of the middle layer within the above range has higher strength, and can reduce the probability of cracks appearing on the outer circle of the wound battery cell and cracks appearing on the edge of the laminated battery cell.
[0116] In some embodiments, the current collector has a thickness of 3 μm-8 μm.
[0117] In some embodiments, the thickness of the current collector may be 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, or any range therebetween.
[0118] The current collector has a low thickness, which can effectively reduce the weight of the battery and is conducive to further improving the energy density of the battery.
[0119] In some embodiments, the thickness of the intermediate layer is 2 μm to 6 μm, and the thickness of the surface layer on one side is 0.5 μm to 2 μm.
[0120] In the present application, the thickness of the intermediate layer and the surface layer on one side can be tested by methods known in the art. As an example, the current collector is cut longitudinally using argon ion polishing technology to test the thickness of each layer.
[0121] In some embodiments, the thickness of the intermediate layer may be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, or any range therebetween.
[0122] In some embodiments, the thickness of the surface layer on one side may be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm or any range therebetween.
[0123] The current collector with the thickness of the intermediate layer and the surface layer within the above range can effectively take into account the strength and bending resistance of the current collector, improve the cycle life of the secondary battery, and enhance the safety of the secondary battery.
[0124] In some embodiments, under the test conditions of room temperature, sample thickness of 6±0.2 μm, and stretching speed of 50±0.5 mm / min, the tensile strength of the current collector is greater than or equal to 900 MPa.
[0125] Herein, the term "room temperature" refers to 20±10°C.
[0126] In some embodiments, under the test conditions of room temperature, sample thickness of 6um±0.2μm, and stretching speed of 50±0.5mm / min, the tensile strength of the current collector can be selected as 900MPa, 950MPa, 1000MPa, 1050MPa, 1100MPa, 1150MPa, 1200MPa, 1250MPa, 1300MPa, 1350MPa, 1400MPa, 1450MPa, 1500MPa or any numerical range therebetween.
[0127] The current collector has high strength, can improve the anti-expansion ability of the battery core, increase the cycle life of the battery, and improve the safety performance of the battery.
[0128] In some embodiments, under the test conditions of room temperature, sample thickness of 6±0.2 μm, and stretching speed of 50±0.5 mm / min, the tensile strength of the current collector is greater than or equal to 1000 MPa.
[0129] A current collector with a tensile strength greater than or equal to 1000 MPa can reduce the risk of premature cracking at the outer ring or edge of the battery cell due to expansion force during the battery cycle, further improving the safety of the battery.
[0130] In some embodiments, under the test conditions of room temperature, sample thickness of 6±0.2 μm, and stretching speed of 50±0.5 mm / min, the tensile strength of the current collector is 1000 MPa-1250 MPa.
[0131] The current collector with a tensile strength within the above range can take into account both strength and bending resistance, thereby comprehensively improving the cycle life of the battery.
[0132] In some embodiments, under the test conditions of room temperature and a sample thickness of 6±0.2 μm, the current collector can be bent for 7 or more times.
[0133] In this application, the test method for the number of bends is to fold the current collector 180°, roll it back and forth at the fold with a 1.5 kg roller, and then unfold it to observe whether cracks and light are visible at the fold, and record the number of rolls required to make cracks and light visible at the fold. The more times the current collector can be folded, the better its bending resistance is, and the less likely it is to break.
[0134] In some embodiments, at room temperature and test conditions of a sample thickness of 6±0.2 μm, the number of times the current collector can be bent can be selected to be 7 times, 8 times, 9 times, 10 times, 11 times, 12 times, 13 times, 14 times, 15 times, 16 times, 17 times, 18 times, 19 times, 20 times or any range of values therebetween.
[0135] The above-mentioned current collector has good bending resistance, which can reduce the probability of premature cracking at the bend inside the battery cell, leading to battery failure, and improve the cycle life of the battery.
[0136] In some embodiments, under the test conditions of room temperature and a sample thickness of 6±0.2 μm, the current collector can be bent 7 to 18 times.
[0137] The current collector with a bendable number of times within the above range can take into account both bending resistance and strength, thereby comprehensively improving the cycle life of the battery.
[0138] On the other hand, the present application provides a method for preparing a current collector, which specifically includes: obtaining an intermediate layer, the intermediate layer including a first metal element, and the mass content of the first metal element is greater than or equal to 80% based on the total mass of the intermediate layer elements; depositing a surface layer on the surface of the intermediate layer to obtain a current collector; the surface layer includes a second metal element, and the mass content of the second metal element is greater than or equal to 80% based on the total mass of the surface layer elements; the tensile strength of the intermediate layer is greater than or equal to the tensile strength of the surface layer, and the bending resistance of the surface layer is greater than or equal to the bending resistance of the intermediate layer.
[0139] The current collector achieves both strength and bending resistance through a multi-layer design. The middle layer has a relatively high tensile strength, and the surface layer has a relatively high bending resistance. The bending resistance of the current collector is improved while maintaining the high strength of the current collector, delaying the time for cracks to appear in the pole piece of the secondary battery during the cycle process, thereby increasing the cycle life of the secondary battery and reducing safety risks.
[0140] In some embodiments, the surface layer is deposited on the surface of the intermediate layer by electroplating, and the electroplating method specifically includes applying current to the electroplating solution so that copper ions in the electroplating solution are reduced and deposited to form the surface layer on the surface of the intermediate layer.
[0141] In this article, the term "electroplating" refers to a method of depositing metal or alloy on the surface of a workpiece to form a metal layer by using the principle of electrolysis.
[0142] In some embodiments, the intermediate layer is also prepared by electroplating.
[0143] In some embodiments, the electric current is direct current and / or alternating current.
[0144] In some embodiments, the electroplating solution includes an additive, and the additive includes one or more of a leveler, a wetting agent, and a brightener.
[0145] As used herein, the term "leveler" refers to a substance added to a plating solution to improve the flatness of the plated layer.
[0146] In this article, the term "wetting agent" refers to a substance used to reduce the interfacial tension between the plating solution / electrode and to achieve better adhesion of the plated layer to the substrate.
[0147] In this article, the term "brightener" refers to a substance that improves the smoothness of the coating and reduces the surface roughness.
[0148] The leveler can adhere to the tip of the copper foil with a fast deposition rate, inhibit the growth of grains, balance the growth rate of pits and tips, and improve the flatness of the copper foil. The wetting agent can improve the wettability of the plating solution and the substrate. The wettability of the plating solution on the cathode is sufficient to achieve rapid electrodeposition with a large current, increase the nucleation rate of the copper foil, and control the average particle size of the grains in the copper foil. The brightener can cooperate with the leveler to adjust the grain size of the copper foil, reduce the surface roughness of the copper foil, and improve the smoothness of the surface.
[0149] In some embodiments, the additives include a leveler, a wetting agent, and a brightener.
[0150] The above three additives cooperate with each other to prepare a surface layer that makes the current collector have both strength and bending resistance.
[0151] In some embodiments, the concentration of the leveler in the plating solution is 40 mg / L-80 mg / L.
[0152] In some embodiments, the concentration of the leveler in the plating solution may be 40 mg / L, 45 mg / L, 50 mg / L, 55 mg / L, 60 mg / L, 65 mg / L, 70 mg / L, 75 mg / L, 80 mg / L or any range therebetween.
[0153] In some embodiments, the concentration of the wetting agent in the electroplating solution is 30 mg / L-80 mg / L.
[0154] In some embodiments, the concentration of the wetting agent in the plating solution may be selected as 30 mg / L, 35 mg / L, 40 mg / L, 45 mg / L, 50 mg / L, 55 mg / L, 60 mg / L, 65 mg / L, 70 mg / L, 75 mg / L, 80 mg / L or any range therebetween.
[0155] The wetting agent having a concentration in the above range in the electroplating solution is conducive to depositing copper grains of appropriate size on the surface layer, taking into account the strength and bending resistance of the current collector, and improving the cycle life of the secondary battery.
[0156] In some embodiments, the concentration of chloride ions in the plating solution is 30 mg / L-60 mg / L.
[0157] In some embodiments, the concentration of chloride ions in the plating solution can be selected as 30 mg / L, 35 mg / L, 40 mg / L, 45 mg / L, 50 mg / L, 55 mg / L, 60 mg / L or any range therebetween.
[0158] In some embodiments, the concentration of copper ions in the electroplating solution is 50 g / L-100 g / L.
[0159] In some embodiments, the concentration of copper ions in the electroplating solution may be 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L, 100 g / L, or any range therebetween.
[0160] In some embodiments, the concentration of the brightener in the plating solution is 10 mg / L-25 mg / L.
[0161] In some embodiments, the concentration of the brightener in the plating solution may be selected as 10 mg / L, 11 mg / L, 12 mg / L, 13 mg / L, 14 mg / L, 15 mg / L, 16 mg / L, 17 mg / L, 18 mg / L, 19 mg / L, 20 mg / L, 21 mg / L, 22 mg / L, 23 mg / L, 24 mg / L, 25 mg / L or any range therebetween.
[0162] In some embodiments, the total mass concentration of the leveler and the brightener in the electroplating solution is less than 100 mg / L.
[0163] In some embodiments, the total mass concentration of the leveler and the brightener in the plating solution may be 70 mg / L, 75 mg / L, 80 mg / L, 85 mg / L, 88 mg / L, 90 mg / L, 95 mg / L or any range therebetween.
[0164] The leveler and brightener in the electroplating solution with a concentration within the above range is conducive to depositing copper grains of appropriate size on the surface layer, taking into account the strength and bending resistance of the current collector, and improving the cycle life of the secondary battery.
[0165] In some embodiments, the electroplating temperature is 50±5°C.
[0166] In some embodiments, the electroplating temperature may be 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, or any range therebetween.
[0167] In some embodiments, the pH of the electroplating solution is 4-7.
[0168] In some embodiments, the pH of the electroplating solution may be 4, 5, 6, 7, or any range therebetween.
[0169] In some embodiments, the leveling agent includes one or more of gelatin and Janus Green; the wetting agent includes one or more of hydroxyethyl cellulose and polyethylene glycol; the brightening agent includes one or more of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate, and thiourea.
[0170] In some embodiments, the electroplating solution includes gelatin at a concentration of 40 mg / L-80 mg / L, hydroxyethyl cellulose at a concentration of 30 mg / L-80 mg / L, sodium polydisulfide dipropane sulfonate at a concentration of 10 mg / L-25 mg / L, copper ions at a concentration of 50 g / L-100 g / L, and chloride ions at a concentration of 30 mg / L-60 mg / L.
[0171] In some embodiments, the plating solution includes gelatin at a concentration of 40 mg / L, 45 mg / L, 50 mg / L, 55 mg / L, 60 mg / L, 65 mg / L, 70 mg / L, 75 mg / L, 80 mg / L or any range therebetween, hydroxyethyl cellulose at a concentration of 30 mg / L, 35 mg / L, 40 mg / L, 45 mg / L, 50 mg / L, 55 mg / L, 60 mg / L, 65 mg / L, 70 mg / L, 75 mg / L, 80 mg / L or any range therebetween, 0mg / L, 15mg / L, 20mg / L, 25mg / L or any range therebetween of sodium polydipropylene sulfide; 50g / L, 55g / L, 60g / L, 65g / L, 70g / L, 75g / L, 80g / L, 85g / L, 90g / L, 95g / L, 100g / L or any range therebetween of copper ions; 30mg / L, 35mg / L, 40mg / L, 45mg / L, 50mg / L, 55mg / L, 60mg / L or any range therebetween of chloride ions.
[0172] In some embodiments, the current density of the direct current is 4000 A / m 2 -8000A / m 2 The electroplating time is 0.5min-3min.
[0173] In some embodiments, the current density of the direct current can be 4000 A / m 2 、4500A / m 2 、5000A / m 2 、5500A / m 2 、6000A / m 2 、6100A / m 2 、6200A / m 2 、6300A / m 2 、6400A / m 2 、6500A / m 2 、6600A / m 2 、6700A / m 2 、6800A / m 2 、6900A / m 2 、7000A / m 2 、7500A / m 2 、8000A / m 2 Or any range of values in between.
[0174] In some embodiments, the time of the electroplating method can be selected as 0.5 min, 1 min, 1.5 min, 2 min, 2.5 min, 3 min or any range therebetween.
[0175] In some embodiments, the preparation method further comprises: heat treating the current collector to obtain an annealed current collector.
[0176] In some embodiments, the heat treatment temperature is 60°C to 80°C.
[0177] In some embodiments, the temperature of the heat treatment may be 60° C., 65° C., 70° C., 75° C., 80° C., or any range therebetween.
[0178] In some embodiments, the heat treatment time is 12 hours to 25 hours.
[0179] In some embodiments, the heat treatment time may be 12 h, 13 h, 14 h, 15 h, 17 h, 20 h, 23 h, 25 h or any range therebetween.
[0180] After annealing, the grain size of the current collector further grows, and the diffraction peak intensity ratio of the (111) crystal plane further decreases, which is beneficial to further improve the bending resistance of the current collector, achieve a balance between the strength and bending resistance of the current collector, and comprehensively improve the cycle life of the secondary battery.
[0181] In some embodiments, the preparation method is a continuous production method.
[0182] On the other hand, the present application provides a composite foil, which includes any feature of the current collector of any embodiment of the present application or any feature of the current collector prepared by the preparation method of any embodiment of the present application.
[0183] In some embodiments, the maximum width of the composite foil is greater than or equal to 1.5 meters, and / or the maximum length of the composite foil is greater than or equal to 10,000 meters.
[0184] In some embodiments, the maximum width of the composite foil is 1.5 meters, 2 meters, 2.5 meters, 3 meters, 3.5 meters, 4 meters, 6 meters, 8 meters, 10 meters, or any range therebetween.
[0185] In some embodiments, the maximum width of the composite foil is 10,000 meters, 15,000 meters, 20,000 meters, 25,000 meters, 30,000 meters, 60,000 meters, 100,000 meters, or any range therebetween.
[0186] The composite foil provided in the embodiments of the present application can be manufactured in large sizes and has prospects for industrial application.
[0187] On the other hand, the present application provides a secondary battery, the secondary battery comprising a pole piece, and the pole piece comprises the current collector provided in the first aspect of the present application.
[0188] In some embodiments, the electrode piece is a positive electrode piece.
[0189] In some embodiments, the electrode piece is a negative electrode piece.
[0190] In some embodiments, the negative electrode plate includes a current collector and a negative electrode film layer disposed on at least one surface of the current collector.
[0191] In some embodiments, the negative electrode film layer includes a negative electrode active material. In some embodiments, the negative electrode active material includes, but is not limited to, one or more of conventional natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide, and tin alloy material.
[0192] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0193] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0194] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.
[0195] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0196] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the present application also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode collector and the negative electrode film layer and disposed on the surface of the negative electrode collector; in some embodiments, the negative electrode plate described in the present application also includes a protective layer covering the surface of the negative electrode film layer.
[0197] On the other hand, the present application further provides an electrical device, comprising a secondary battery according to any embodiment of the present application, wherein the secondary battery may be in the form of a battery cell, a battery module or a battery pack.
[0198] The present application has no particular restrictions on the type of secondary battery. For example, the secondary battery can be a lithium-ion battery, etc. In general, a secondary battery includes a positive electrode plate, a negative electrode plate, and an electrolyte, etc. During the charge and discharge process of the secondary battery, active ions are embedded and removed back and forth between the positive electrode plate and the negative electrode plate, and the electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate. The present application has no particular restrictions on the type of the electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (ie, an electrolyte). Secondary batteries using electrolytes and some secondary batteries using solid electrolytes may also include a separator, which is arranged between the positive electrode plate and the negative electrode plate to play an isolation role.
[0199] [Positive electrode]
[0200] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0201] The positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0202] The positive electrode film layer generally includes a positive electrode active material, an optional binder, and an optional conductive agent. The positive electrode film layer is usually formed by coating a positive electrode slurry on the positive electrode current collector and then drying and cold pressing. The positive electrode slurry is usually formed by dispersing a positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring evenly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto. As an example, the binder for the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin. As an example, the conductive agent for the positive electrode film layer includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0203] The positive electrode active material can be a positive electrode active material for secondary batteries well-known in the art.
[0204] When the secondary battery of the present application is a lithium ion battery, the positive electrode active material may include, but is not limited to, one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds. Examples of the lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the lithium-containing phosphates may include, but are not limited to, lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their respective modified compounds.
[0205] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a lithium transition metal oxide having the general formula Li a Ni b Co c M d O e A f and its modified compounds. 0.8 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A is selected from one or more of N, F, S, and Cl.
[0206] In some embodiments, as an example, the positive electrode active material for the lithium ion battery may include LiCoO2 、LiNiO 2 、LiMnO 2 、LiMn 2 O 4 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05 O 2 、LiFePO 4 and LiMnPO 4 One or more of .
[0207] In the present application, the modified compound of each positive electrode active material mentioned above may be a compound obtained by doping and / or surface coating the positive electrode active material.
[0208] [Electrolytes]
[0209] In some embodiments, the electrolyte is an electrolyte solution, and the electrolyte solution includes an electrolyte salt and a solvent.
[0210] The type of the electrolyte salt is not particularly limited and can be selected according to actual needs.
[0211] When the secondary battery of the present application is a lithium ion battery, the electrolyte salt may include lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2), one or more of lithium difluorobis(oxalate) phosphate (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP).
[0212] The type of the solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) One or more.
[0213] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high temperature performance of the secondary battery, and additives that improve the low temperature power performance of the secondary battery.
[0214] [Isolation film]
[0215] The present application has no particular limitation on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.
[0216] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.
[0217] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly by a winding process or a lamination process.
[0218] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0219] In some embodiments, the outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0220] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 The secondary battery 5 is a square structure as an example.
[0221] In some embodiments, Figure 5 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.
[0222] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the secondary battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0223] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0224] Figure 6 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 6 As shown, in the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0225] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0226] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0227] Figure 7 and Figure 8 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 7 and Figure 8 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0228] Electrical devices
[0229] The present application also provides an electrical device, which includes at least one of the secondary battery, battery module or battery pack of the present application. The secondary battery, battery module or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0230] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0231] Fig. 9 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0232] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0233] Example
[0234] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0235] Example 1
[0236] (1) Preparation of composite foil
[0237] First, prepare a ferric sulfate solution with a concentration of 20g / L and a pH value of 6-7, and pour the solution into the Hall cell to complete the solution preparation; then add gelatin as a leveling agent, sodium polydisulfide propane sulfonate (SPS) as a brightener, and hydroxyethyl cellulose as a wetting agent to the solution, wherein the gelatin concentration is 70mg / L, the brightener concentration is 25mg / L, and the wetting agent concentration is 50mg / L; the solution is heated to 50℃-55℃, and the current density is controlled at 5000A / m 2 The Fe foil with a thickness of 4 μm was generated by electroplating for about 3 minutes, and the average grain size of the Fe foil was 0.2 μm.
[0238] With Fe foil as the middle layer, the generated Fe foil is placed in a solution containing copper sulfate, the pH is controlled at 3-5, the middle layer is connected to the negative electrode current, the copper sulfate concentration is 80g / L, the sodium chloride concentration is 37mg / L, the leveling agent gelatin concentration is 70mg / L, the brightener sodium polydisulfide dipropane sulfonate (SPS) concentration is 25mg / L, the wetting agent hydroxyethyl cellulose (HEC) concentration is 50mg / L, the solution temperature is raised to 50℃~55℃, and the current density is controlled at 6000A / m 2 The electroplating time is about 2min to 3min, and copper foil with a thickness of 1μm is generated on the upper and lower surfaces of the Fe foil, forming a Cu / Fe / Cu composite foil with a thickness of 6μm. In addition to the inevitable impurity elements in the surface layer, the main component element is Cu; in addition to the inevitable impurity elements in the middle layer, the main component element is Fe.
[0239] (2) Preparation of batteries
[0240] Preparation of positive electrode
[0241] According to the mass ratio of lithium iron phosphate: conductive carbon black: PVDF = 8:1:1, the solvent N-methylpyrrolidone is added, and coated on both sides of the aluminum foil. After cold pressing and cutting, the positive electrode sheet is obtained, and the positive electrode sheet is rolled into a film roll, and the ceramic slurry is sprayed on the cut surface of the film roll. In the ceramic slurry, the ceramic material is boehmite, accounting for 39wt%; the binder is polyacrylate, accounting for 5wt%; the solvent is N-methylpyrrolidone, the solid content of the slurry is 10%, and the viscosity of the slurry is 800mPa·s.
[0242] Preparation of negative electrode
[0243] Artificial graphite, conductive carbon black, binder carboxymethyl cellulose (CMC) and solvent water are uniformly mixed in a weight ratio of 1.1% SBR + 0.9% CMC + 0.7% SP + 97.3% graphite, coated on both sides of the composite foil prepared above, and cold pressed and cut to obtain a negative electrode sheet.
[0244] Preparation of diaphragm
[0245] A polyethylene film with a thickness of 13 μm was used as the separator.
[0246] Preparation of electrolyte
[0247] Ethylene carbonate, diethyl carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1:1, and LiPF 6 Dissolved in the above solution to obtain an electrolyte. In the electrolyte, LiPF 6 The concentration is 1 mol / L.
[0248] Battery Assembly
[0249] Placed in the order of "diaphragm-negative electrode sheet-diaphragm-positive electrode sheet", one end of the positive electrode sheet, negative electrode sheet and two separators are fixed to the discharge roller, and the other end is stacked together and fixed to the winding shaft. The winding shaft is rotated by a motor to wind up the positive electrode sheet, negative electrode sheet and two separators to obtain a wound battery.
[0250] Example 2-3
[0251] The preparation method of Example 2-3 is basically the same as that of Example 1, except that the components of the plating solution in the surface layer deposition step are changed, as shown in Table 1.
[0252] Example 4
[0253] The preparation method of Example 4 is substantially the same as that of Example 1, except that the current collector prepared in Example 1 is subjected to heat treatment at a temperature of 80° C. for 12 h.
[0254] Comparative Example 1-2
[0255] The preparation method of Comparative Example 1-2 is basically the same as that of Example 1, except that the components of the plating solution in the surface layer deposition step are adjusted, as shown in Table 1.
[0256] Comparative Example 3
[0257] The preparation method of Comparative Example 3 is substantially the same as that of Example 1, except that iron foil is used as the negative electrode current collector, and the thickness of the iron foil is 6 micrometers.
[0258] Comparative Example 4
[0259] The preparation method of Comparative Example 4 is basically the same as that of Example 1, except that conventional high-strength copper foil is used as the negative electrode current collector, and the thickness of the copper foil is 6 microns.
[0260] Table 1
[0261]
[0262] Test Method
[0263] (1) State of Health (SOH) corresponding to cracks in the battery cell
[0264] At 25°C, the battery is charged at a constant current of 1C to a voltage of 3.8V, then charged at a constant voltage of 3.8V to a current ≤0.05C, and then discharged at a constant current of 1C to a voltage of 2.5V. This is a charge and discharge process, and the charge and discharge cycle is repeated in this way. Then, electronic computed tomography (CT) is used to determine whether cracks have occurred inside the battery, and the residual state of charge (SOH) when cracks appear in the battery is recorded. A fresh battery cell is 100% SOH. With the loss of active ions during the battery cell cycle, the residual state of charge of the battery cell continues to decrease. The larger the SOH corresponding to the cracks in the battery cell, the more likely the battery cell is to crack in the early stages of the cycle, and the battery cycle life is low. On the contrary, the smaller the SOH corresponding to the cracks in the battery cell, the more likely the battery cell will crack in the later stages of the cycle, and the battery cycle life is relatively high.
[0265] Test Results
[0266] The test results are shown in Table 2.
[0267] Table 2
[0268]
[0269] The conventional general-strength copper foil in Comparative Example 4 has low tensile strength, and cracks preferentially appear at the outer ring of the battery cell where the expansion force is the largest during the battery cycle. Although the iron foil in Comparative Example 3 has high tensile strength, it has poor bending resistance, and cracks preferentially appear at the inner ring of the battery cell where the bending deformation is large during the battery cycle. From the comparison between the embodiment and the comparative example, it can be seen that the surface layer is copper foil, and the average grain size of the surface layer is greater than or equal to 1.7μm; the current collector with an intermediate layer of iron foil can withstand more cycle expansion, and the SOH corresponding to cracks in the battery cell is less than or equal to 60%, which helps to improve the cycle life and safety performance of the secondary battery, so that the battery pole piece will not break within the expected service life (such as the warranty period), meeting the market demand for the use of secondary batteries.
[0270] From the comparison between the embodiment and comparative example 1, it can be seen that the total mass concentration of the leveler and the brightener in the electroplating solution is less than 100 mg / L, which is beneficial to reduce nucleation, increase the average size of the copper grains in the surface layer, and improve the bending resistance of the current collector. From the comparison between the embodiment and comparative example 2, it can be seen that the concentration of the wetting agent in the electroplating solution is 30 mg / L-80 mg / L, which is beneficial to reduce nucleation, increase the average size of the copper grains in the surface layer, and improve the bending resistance of the current collector.
[0271] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A current collector, characterized in that: The current collector includes a surface layer and an intermediate layer arranged between the surface layers, the intermediate layer includes a first metal element, and the total mass content of the first metal element is greater than or equal to 80% based on the total mass of the intermediate layer elements, and the surface layer includes a second metal element, and the total mass content of the second metal element is greater than or equal to 80% based on the total mass of the surface layer elements; the tensile strength of the intermediate layer is greater than or equal to the tensile strength of the surface layer, and the bending resistance of the surface layer is greater than or equal to the bending resistance of the intermediate layer.
2. The current collector according to claim 1, characterized in that: The first metal element includes one or more of Fe, Sn, Ni, and Zn.
3. The current collector according to claim 1 or 2, characterized in that: The second metal element includes Cu.
4. The current collector according to any one of claims 1 to 3, characterized in that: The average grain size of the surface layer is greater than or equal to 1.7 μm.
5. The current collector according to any one of claims 1 to 4, characterized in that: The average grain size of the surface layer is 1.7 μm-3.5 μm.
6. The current collector according to any one of claims 1 to 5, characterized in that: The average grain size of the surface layer is 1.9 μm to 2.5 μm.
7. The current collector according to any one of claims 1 to 6, characterized in that: The diffraction intensity of the (111) crystal plane in the surface layer accounts for 20%-40% of the total diffraction intensity of the (111) crystal plane, (200) crystal plane, (220) crystal plane, (311) crystal plane and (222) crystal plane in the surface layer.
8. The current collector according to any one of claims 1 to 7, characterized in that: The diffraction intensity of the (111) crystal plane in the surface layer accounts for 25% to 35% of the total diffraction intensity of the (111) crystal plane, (200) crystal plane, (220) crystal plane, (311) crystal plane, and (222) crystal plane in the surface layer.
9. The current collector according to any one of claims 1 to 8, characterized in that: The average grain size of the intermediate layer is 0.1 μm-1 μm.
10. The current collector according to any one of claims 1 to 9, characterized in that: The thickness of the current collector is 3 μm-8 μm.
11. The current collector according to any one of claims 1 to 10, characterized in that: The thickness of the intermediate layer is 2 μm to 6 μm, and the thickness of the surface layer on one side is 0.5 μm to 2 μm.
12. The current collector according to any one of claims 1 to 11, characterized in that: Under the test conditions of room temperature, sample thickness of 6±0.2 μm, and stretching speed of 50±0.5 mm / min, the tensile strength of the current collector is greater than or equal to 900 MPa.
13. The current collector according to any one of claims 1 to 11, characterized in that: Under the test conditions of room temperature, sample thickness of 6±0.2 μm, and stretching speed of 50±0.5 mm / min, the tensile strength of the current collector is greater than or equal to 1000 MPa.
14. The current collector according to any one of claims 1 to 11, characterized in that: Under the test conditions of room temperature, sample thickness of 6±0.2 μm, and stretching speed of 50±0.5 mm / min, the tensile strength of the current collector is 1000 MPa-1250 MPa.
15. The current collector according to any one of claims 1 to 14, characterized in that: Under the test conditions of room temperature and a sample thickness of 6±0.2 μm, the current collector can be bent for 7 or more times.
16. The current collector according to any one of claims 1 to 14, characterized in that: Under the test conditions of room temperature and a sample thickness of 6±0.2 μm, the current collector can be bent 7 to 18 times.
17. A secondary battery, characterized in that: It comprises a pole piece, wherein the pole piece comprises the current collector according to any one of claims 1 to 16.
18. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 17.
19. A method for preparing a current collector, characterized in that: The preparation method specifically comprises: Obtaining an intermediate layer, the intermediate layer comprising a first metal element, wherein the mass content of the first metal element is greater than or equal to 80% based on the total mass of the elements in the intermediate layer; A surface layer is deposited on the surface of the intermediate layer to obtain a current collector; the surface layer includes a second metal element, and the mass content of the second metal element is greater than or equal to 80% based on the total mass of the surface layer elements; the tensile strength of the intermediate layer is greater than or equal to the tensile strength of the surface layer, and the bending resistance of the surface layer is greater than or equal to the bending resistance of the intermediate layer.
20. The preparation method according to claim 19, characterized in that: The surface layer is deposited on the surface of the intermediate layer by electroplating. The electroplating method specifically includes applying current to the electroplating solution so that the copper ions in the electroplating solution are reduced and deposited to form the surface layer on the surface of the intermediate layer.
21. The preparation method according to claim 20, characterized in that: The electroplating solution includes additives, and the additives include one or more of a leveler, a wetting agent, and a brightener.
22. The preparation method according to claim 21, characterized in that: The additives include leveling agents, wetting agents and brighteners.
23. The preparation method according to any one of claims 19 to 22, characterized in that: The electroplating solution meets one or more of the following conditions: (1) The concentration of the leveling agent in the electroplating solution is 40 mg / L-80 mg / L; (2) The concentration of the wetting agent in the electroplating solution is 30 mg / L-80 mg / L; (3) The concentration of chloride ions in the plating solution is 30 mg / L-60 mg / L; (4) The concentration of copper ions in the electroplating solution is 50 g / L-100 g / L; (5) The concentration of the brightener in the plating solution is 10 mg / L-25 mg / L; (6) The total mass concentration of the leveling agent and the brightener in the plating solution is less than 100 mg / L; (7) The electroplating temperature is 50±5°C; (8) The pH of the electroplating solution is 4-7.
24. The preparation method according to any one of claims 19 to 23, characterized in that: The leveling agent includes one or more of gelatin and Janus Green; the wetting agent includes one or more of hydroxyethyl cellulose and polyethylene glycol; the brightening agent includes one or more of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate, and thiourea.
25. The preparation method according to any one of claims 19 to 24, characterized in that: The electroplating solution includes gelatin with a concentration of 40 mg / L-80 mg / L, hydroxyethyl cellulose with a concentration of 30 mg / L-80 mg / L, sodium polydisulfide dipropane sulfonate with a concentration of 10 mg / L-25 mg / L, copper ions with a concentration of 50 g / L-100 g / L, and chloride ions with a concentration of 30 mg / L-60 mg / L.
26. The preparation method according to any one of claims 19 to 25, characterized in that The current density of the direct current is 4000A / m 2 -8000A / m 2 The electroplating time is 0.5 minutes to 3 minutes.
27. The preparation method according to any one of claims 19 to 26, characterized in that: The preparation method further comprises: The current collector is thermally treated to obtain an annealed current collector.
Citation Information
Patent Citations
Positive electrode, preparation method thereof and supercapacitor
CN116564715A
Copper foil, negative electrode current collector and negative electrode material for non-aqueous secondary battery
US20150132658A1